2000
DOI: 10.1042/bj3490169
|View full text |Cite
|
Sign up to set email alerts
|

The pepsin residue glycine-76 contributes to active-site loop flexibility and participates in catalysis

Abstract: Glycine residues are known to contribute to conformational flexibility of polypeptide chains, and have been found to contribute to flexibility of some loops associated with enzymic catalysis. A comparison of porcine pepsin in zymogen, mature and inhibited forms revealed that a loop (a flap), consisting of residues 71-80, located near the active site changed its position upon substrate binding. The loop residue, glycine-76, has been implicated in the catalytic process and thought to participate in a hydrogen-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The highly conserved residue Gly76 likely enables this unusual conformation,19 since it adopts a positive torsion angle, φ, in PrA and bovine chymosin, whereas in other pepsin‐like aspartic proteinases Gly76 has a negative torsion angle. This proposal is consistent with work done in our laboratory which suggested that the role of Gly76 in porcine pepsin was the contribution of flexibility to the flap region 40…”
Section: Structuresupporting
confidence: 92%
“…The highly conserved residue Gly76 likely enables this unusual conformation,19 since it adopts a positive torsion angle, φ, in PrA and bovine chymosin, whereas in other pepsin‐like aspartic proteinases Gly76 has a negative torsion angle. This proposal is consistent with work done in our laboratory which suggested that the role of Gly76 in porcine pepsin was the contribution of flexibility to the flap region 40…”
Section: Structuresupporting
confidence: 92%
“…Indeed, the size and shape of the protein do not change significantly upon confining the pepsin-containing droplet in a mesopore, even at partial dehydration conditions, as can be also deduced from the data in Table 2, and from the superposition of the 0–20 ns configurations (Figure 5). On the whole, and in analogy with what observed for flat silica surfaces, these results suggest therefore that the pepsin catalytic properties [62,86] are maintained in a water nanodroplet confined in mesoporous silicas.…”
Section: Resultssupporting
confidence: 79%
“…From the sequence analysis of the flap‐structure, it can be seen the PlmIV has a glycine residue situated at the flap tip (Gly78). The inherent flexibility of glycine accounts for the mobility and increased flexibility observed in PlmIV . Glycine is the smallest amino acid, due to it being achiral, with two hydrogen atoms composing the side chain.…”
Section: Resultsmentioning
confidence: 99%